Congenital diaphragmatic hernia-does the presence of a hernia sac improve outcome? A systematic review of published studies - Raitio A; Salim A; Losty PD (SPRINGER, 2022)
Early reports have suggested survival benefits associated with a hernia sac in congenital diaphragmatic hernia (CDH). However, these studies have included only small subsets of patients. This systematic review aimed to evaluate differences in outcomes of CDH newborns with and without a hernia sac. PubMed and Embase databases were searched using relevant key terms. Papers were independently reviewed by two authors with final selection approved by the senior author. Original search retrieved 537 papers; the final review included 8 studies (n = 837 patients). There were 168 CDH patients (20%) with a hernia sac with an overall survival of 93% vs 73% for CDH newborns without a sac (p < 0.001). Twenty-three percent of patients with a CDH sac required diaphragm patch repair vs 44% patients without a sac (p < 0.001). Pulmonary hypertension was manifested in 44% of CDH babies with a hernia sac vs 64% without a sac (p < 0.001). Three studies compared ECMO requirement: 15% with a hernia sac and 34% without sac,p < 0.001.Conclusion: This study shows significant survival benefits in newborns associated with presence of a CDH sac. This may be likely related to these infants having more favourable physiology with less severe pulmonary hypertension and/or smaller anatomical defects requiring primary closure only.